2016
DOI: 10.1155/2016/5287697
|View full text |Cite
|
Sign up to set email alerts
|

Venous Adventitial Cystic Disease: A Review of 45 Cases Treated Since 1963

Abstract: Purpose. To review and identify the most accurate ways of diagnosing and treating adventitial cystic disease (ACD) of the venous system. Methods. Cases of ACD were collected through three popular medical databases, including PubMed, Cochrane, OVID, and MEDLINE. After reviewing the literature, the sites of occurrence of 323 cases of adventitial cystic disease were documented, and all cases of arterial ACD were excluded. The clinical features, treatment, and subsequent course of 45 cases of venous ACD are includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 28 publications
1
39
0
3
Order By: Relevance
“…The condition is often misdiagnosed as deep vein thrombosis (DVT), femoral aneurysm, venous tumor, or lymphadenopathy. Bascone et al [ 3 ] performed a collective review of 45 cases of venous ACD for 50 years (from 1963 to 2016). Based on the results, the most common site was the femoral vein (56%), followed by the EIV (24%), saphenous vein and others (13%), and popliteal vein (7%).…”
Section: Literature Review Of Venous Acdmentioning
confidence: 99%
See 3 more Smart Citations
“…The condition is often misdiagnosed as deep vein thrombosis (DVT), femoral aneurysm, venous tumor, or lymphadenopathy. Bascone et al [ 3 ] performed a collective review of 45 cases of venous ACD for 50 years (from 1963 to 2016). Based on the results, the most common site was the femoral vein (56%), followed by the EIV (24%), saphenous vein and others (13%), and popliteal vein (7%).…”
Section: Literature Review Of Venous Acdmentioning
confidence: 99%
“…This theory cannot explain cyst recurrence after complete cyst excision and within bypass grafts and rapid recurrences within a few months. Furthermore, the mean age of the patients was reported to be 47 years [ 3 ], and it is hard to believe that the ectopic synovial cells suddenly activate and secrete mucin after a long silent period of over 40 years. And this disease was observed only in one patient from the pediatric age group.…”
Section: Theories On the Possible Etiology And Pathogenesis Of Acdmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A literature review described a 45-case collection of venous ACDs reported from 1947 to 2016. 2 We describe a patient with venous ACD of the external iliac vein (EIV) who underwent surgical treatment. Written informed consent was obtained from the patient for publication of this case report and accompanying images.…”
mentioning
confidence: 99%